Using Blended Learning to Develop Vocational High School English Writing Material - Abdullah Farih; Maulidifi Ajrin Karimata (Acitya: Journal of Teaching and Education, 2022)
The objective of this study is using blended learning to develop vocational high school English writing material. It tries to develop writing material based on blended learning in vocational high school. This study is research and development (R&D) adapted by Sugiyono’s model. There are nine stages applied in the study. They are (1) need survey, (2) design product, (3) design validation, (4) design revision, (5) try out 1, (6) product revision, (7) try out 2, (8) final product revision, (9) production. The try out place at tenth grade of SMK Negeri 1Lamongan. The data gained through interviews, questionnaires and observations checklist. The interviews are for students need and teachers need. Questionnaires are to do the concept analysis, to submit the experts’ appraisal and to get the student’s responses. Furthermore, the observation checklist is used to conduct developing testing. The result of the study is (1) all of students enthusiastic in blended learning method for writing English learning. The third conclusion, the students of SMK Negeri 1 Lamongan gave positive response to all the activities in “Writing Blended Learning” book. They were appreciating and feeling helpful during in writing English class. The last conclusion is using the Writing Blended Learning handbook can help students improve their English writing skills and made the students more excited when learning English writing. Finally, the product of the study is the handbook entitled “Writing Blended Learning” which comprises 9 materials divided into two semesters